To name and control - Paulo Pachá (Mélanges de la Casa de Velázquez, 2019)
This paper’s objective is to analyze the transformations in Visigothic provincial organization, as related to the development of the integration process of the Visigothic Kingdom of Toledo. To achieve this objective, I divided the paper in three sections: in the first I defined what I call the integration process; in the second I discussed how two central processes changed the kingdom’s provincial organization—the affirmation of Toledo as metropolitan see and the creation of new bishoprics in the peninsular south; and, lastly, in the third section I proposed an alternative interpretation for the creation of new bishoprics by king Wamba (672-680). The paper conclusion indicated that the dynamic character of the provincial organization was directly related to the dynamic character of Visigothic power relations in the Iberian Peninsula.